Ethical dilemmas in assisted reproduction; Perspectives from a developing country (2017)
Background: Ethical dilemmas continue to unfold as a result of the expanding roles of assisted reproduction. Understanding the basic ethical principles of Autonomy, Justice, Beneficence and Non-maleficence as key components of practice when providing advanced fertility management cannot be over emphasized. Ethics simply refers to the moral principles that govern a person or groups behavior. It is also defined as a code of moral principles derived from a system of values and beliefs that help define the correctness of our actions. Critical opinions have been expressed in the area of commodification of human tissue. There are also growing concerns about cross border reproductive care and its implication on reproductive health. Since ethical dilemmas may not be resolved at once, continuous appraisal of the current situation with the aim of developing locally relevant ethical frameworks is desirable. Examining these ethical concerns which confront our daily practices is not only pertinent but expedient as there has been a gradual expansion of assisted conception services in Nigeria.